Structural validation of the “Teacher’s report form” attention problems scale in a Brazilian sample - Thiago Pires; Marina Rocha; Simone Assis; Flavio Nobre (Measurement Instruments for the Social Sciences, 2021)
Abstract Background Attention deficit hyperactivity disorder is one of the most common childhood neurodevelopmental syndromes. Although clinical evaluation is considered the gold standard in diagnosing psychiatric disorders, in epidemiological studies, this evaluation is rarely used for practical and financial reasons. Instead, psychometric instruments are used to screen for the disorders. In this case, it is essential to investigate whether these instruments are suitable for measuring the proposed problem. This study aims to verify the structural validation of the Attention Problems Scale of the Teacher’s Report Form (TRF). Methods A random sample of 445 TRF filled out by the teacher of children from São Gonçalo/RJ was selected. The confirmatory factor analysis was applied to validate some factor structures that have been raised in the literature. A second aspect analyzed was the use of structural equation models to verify the validated factorial structure’s relationship with some comorbidities. Results The bifactor model was the most suitable to explain the TRF child’s Attention Problems Scale’s factor structure. It presented the best-fit quality scores for confirmatory factor analysis than other tested structures. Although it presented good indicators for structural validity, some symptoms could be reassessed to have a more consistent instrument. The bifactor model as an explanatory structure in SEM was able to predict important mental health outcomes. These results are an additional validation to the bifactor model. Conclusions The results suggest the validity of the TRF’s Attention Problems Scale. The instrument’s factor structure was also appropriate because it corroborated most of the association’s assumptions between subtypes of attention problems and other aspects of mental health. The existence of screening scales adapted to Brazilian Portuguese can substantially impact many children who have difficulty learning. Also, the screening scales can be a useful tool for the health sector to facilitate referral to the professional to make the diagnosis.